Corrigendum to “Zeaxanthin: Review of Toxicological Data and Acceptable Daily Intake” - James A. Edwards; Dirk Cremer (Journal of Ophthalmology)
Zeaxanthin is a nutritional carotenoid with a considerable amount of safety data based on regulatory studies, which forms the basis of its safety evaluation. Subchronic OECD guideline studies with mice and rats receiving beadlet formulations of high-purity synthetic zeaxanthin in the diet at dosages up to 1000 mg/kg body weight (bw)/day, and in dogs at over 400 mg/kg bw/day, produced no adverse effects or histopathological changes. In developmental toxicity studies, there was no evidence of fetal toxicity or teratogenicity in rats or rabbits at dosages up to 1000 or 400 mg/kg bw/day, respectively. Formulated zeaxanthin was not mutagenic or clastogenic in a series of in vitro and in vivo tests for genotoxicity. A 52-week chronic oral study in cynomolgus monkeys at doses of 0.2 and 20 mg/kg  bw/day, mainly designed to assess accumulation and effects in primate eyes, showed no adverse effects. In a two-generation study in rats, the NOAEL was 150 mg/kg  bw/day. In 2012, this dosage was used by EFSA (NDA Panel), in association with a 200-fold safety factor, to propose an acceptable daily intake equivalent to 53 mg/day for a 70 kg adult. The requested use level of 2 mg/day was ratified by the EU Commission. Recent reevaluation of the data from the two-generation study indicated that the NOAEL should be redefined as the high dosage of 500 mg/kg bw/day, rather than the intermediate dosage of 150 mg/kg bw/day. The NOAEL of this study was formally amended to the high dosage. Also in 2018, JECFA raised the group ADI of lutein and zeaxanthin to “not specified,” due to the low toxicity of these substances.